Improving Ability To Explore Text Structure Through Learning Models Cooperative Integrated Reading And Composition (Circ) Class VIII Students SMP Negeri 3 Gunungsitoli Utara - Leni Nofryanti Lase (Indonesian Journal of Education and Mathematical Science, 2020)
This research is a Classroom Action Research (CAR) which aims to improve the ability of class VIII students of SMP Negeri 3 Gunungsitoli Utara in 2019/2020 in examining the structure of explanatory text using the Cooperative Integrated Reading and Composition learning model.Based on the results of the study, there was an increase in the students' ability in examining the structure of explanatory text, seen in the first cycle with an average value of 57.66, the lowest score was 48, the highest score was 80, while in the second cycle, the average value was 82.83, the lowest score. 72, the highest score was 96. The results of the observation of student activities in the first cycle of the first meeting were 56.66% and the second meeting was 64.58%, while in the second cycle the first meeting was 76.25% and the second meeting was 95.23%. The results of observations of researchers (teachers) in the first cycle of the first meeting were 43.75% and the second meeting was 56.25%, while the second cycle of the first meeting was 68.75% and the second meeting was 100%.Based on the explanation above, the researchers conclude that: 1) using a model (CIRC) can improve students' ability to study the explanatory text structure of class VIII students of SMP Negeri 3 Gunungsitoli Utara for the 2019/2020 Academic Year, 2) using the learning model (CIRC) can increase motivation in examining the explanatory text structure of class VIII students of SMP Negeri 3 Gunungsitoli Utara for the 2019/2020 academic year. Suggestion 1) for teachers of Indonesian Language and Literature subjects at SMP Negeri 3 Gunungsitoli Utara, research using a learning model (CIRC) should be used by teachers in learning to examine explanatory text structures, 2) for students at SMP Negeri 3 Gunungsitoli Utara, this research can provide motivation to students to examine the structure of explanatory text.